A magnetic micro-environment in scaffolds for stimulating bone regeneration. (5th January 2020) - Shuai, Cijun; Yang, Wenjing; He, Chongxian; Peng, Shuping; Gao, Chengde; Yang, Youwen; Qi, Fangwei; Feng, Pei
Abstract: In present study, a strategy is presented to construct a magnetic micro-environment in poly-l -lactide/polyglycolic acid (PLLA/PGA) scaffolds fabricated via selective laser sintering by incorporating Fe3 O4 magnetic nanoparticles (MNPs), aiming to enhance cell viability and promote bone regeneration. In the micro-environment, each nanoparticle provides a nanoscale magnetic field to activate cellular responses. The results in vitro demonstrated that the magnetic scaffolds not only stimulated cell adhesion and viability, but also enhanced proliferation rate and alkaline phosphatase activity. Meanwhile, the compressive strength and modulus were increased by 81.9% and 71.6%, respectively, which were determined by the rigid enhancement effect of MNPs. Moreover, the magnetic scaffolds were implanted into rabbit radius bone defect in vivo, and the results indicated that the magnetic scaffolds significantly induced substantial blood vessel tissue, fibrous tissue and new bone tissue formation at 2 months post-implantation, revealing the excellent bone regeneration capability. These positive results indicate that the construction of magnetic micro-environment in scaffolds is a working countermeasure to promote bone regeneration. Graphical abstract: Image 1 Highlights: A magnetic micro-environment was constructed in PLLA/PGA scaffolds by incorporating Fe3 O4 MNPs. The magnetic nanoparticle provides a nanoscale magnetic field to activate cellular responses. Magnetic scaffolds promoted cell adhesion, proliferation and differentiation. The new bone tissue formation was significantly accelerated.